Sistem Penunjang Keputusan Pemasaran Pada Koperasi Simpan Pinjam Keluarga Sejahtera dengan Metode AHP - Tammayyusdin, Aulia Salma; Sandra, Gardika; Laureta, Wika Widya; Sulistyowati, Daning Nur (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This study discusses the marketing decision support system in the prosperous family savings and loan cooperatives, as a cooperative that provides financial services provided by the general public to make savings and loans in increasing economic stability. With this pandemic, people experience a decline in financial factors that result in financial disruption and constraints for daily life. In this study, the general public will know the programs carried out by cooperative members in spreading marketing among the surrounding community or even PKK women who have social environmental organizations. This process is carried out by the Prosperous Family Cooperative, which is resolved in a structured selection. As a source of information about the process carried out in marketing to make it easier for companies to consider the largest number in the number of people who get information about the Prosperous Family Cooperative. The method used in this study was carried out to take a decision in the final selection which was obtained through the ratio value. This study aims to provide an explanation regarding marketing information using the Analytical Hierarchy Process (AHP) method, in order to get the value of marketing priorities carried out by the Prosperous Family Cooperative. The results obtained in using a marketing decision support system in a prosperous family savings and loan cooperative using the AHP method is direct selling to the public